Identification of the most relevant factors that affect and reflect the quality of granules by application of canonical and cluster analysis - Dias, VH (2015)
The production of granules by wet granulation in a fluidized bed was assessed according to two statistical techniques to identify the most relevant factors that affect the quality of the granules. The statistics used include Canonical Analysis and Cluster Analysis. The factors studied, according to a center of gravity design, included the solubility of a model drug, different grades of polyvinylpirrolidone (PVP), the polarity and the rate of administration of the granulation solution, the atomizing air pressure, the inlet air pressure and rate. The properties of the granules considered were the yield, the assay of the drug, the size, the densities (true, bulk and tapped), the friability, the flowability and one compressibility index. Statistical analysis of the factors evaluated has shown that the solubility of the materials and the pressure of the atomizing air in the nozzle were the most critical parameters affecting the quality of the granules. Less relevant were the granulation solution and the grade of PVP. The properties of the granules that best described their quality were the yield and the densities. From the Cluster Analysis it was possible to divide the granules in two clusters, where cluster 1 was identifiable by the yield, the assay, the flowability, and the friability, whereas cluster 2 was better identified by the size of the granules. (C) 2002 Wiley-Liss, Inc. and the American Pharmaceutical Association.